2001
DOI: 10.1089/104303401750214258
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Stem Cell Gene Therapy of Arylsulfatase A-Deficient Mice, Using an Arylsulfatase A Mutant That Is Hypersecreted from Retrovirally Transduced Donor-Type Cells

Abstract: Arylsulfatase A (ASA)-deficient mice represent an animal model for the fatal lysosomal storage disease metachromatic leukodystrophy, which is characterized by widespread intralysosomal deposition of sulfatide. Bone marrow stem cell gene therapy in mice, using a retroviral vector mediating expression of wild-type human ASA, has the potential to ameliorate the visceral pathology, but improves the prevailing brain disease and neurologic symptoms only marginally. One factor that influences the efficacy of bone mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…By performing detailed neurophysiological studies of MLD mice, we found significant impairments of central and peripher-al motor conduction (MCV reduction, increased F wave, MEP and CCT latencies), which provide useful functional parameters to monitor disease progression and therapeutic efficacy, and were not evaluated or assessable in previous studies (3,25,47,48). Behavioral tests demonstrated a clear decline in motor learning and coordination in aging MLD mice.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…By performing detailed neurophysiological studies of MLD mice, we found significant impairments of central and peripher-al motor conduction (MCV reduction, increased F wave, MEP and CCT latencies), which provide useful functional parameters to monitor disease progression and therapeutic efficacy, and were not evaluated or assessable in previous studies (3,25,47,48). Behavioral tests demonstrated a clear decline in motor learning and coordination in aging MLD mice.…”
Section: Discussionmentioning
confidence: 80%
“…Previous transplantation studies using retroviral vector-transduced BM cells failed to observe significant benefits in NS pathology and functional parameters in MLD mice (47,48). It is likely that the successful outcome of our approach was dependent on the efficient HSC transduction and robust gene expression in their vascular and extravascular progeny reached by the optimized LVs and conditions used in this study.…”
Section: Discussionmentioning
confidence: 88%
“…The most extensive studies have been performed in a model of metachromatic leukodystrophy and initially used donor cells modifi ed by fi rst-generation ␥ -retroviral vectors which demonstrated a modest correction of the neuropathology in the mouse model ( 150 ). Subsequent studies using more effi cient lentiviral-based vectors that transduced a greater number of the donor hematopoietic stem cells and that resulted in the secretion of higher levels of the enzyme (i.e., arylsulfatase A) completely prevented the development of neuropathology and behavioral abnormalities in mice ( 141,151 ).…”
Section: Effi Cacy Of Intracranial Delivery Of Aav Vectors For Neuropmentioning
confidence: 99%
“…The proteins included the Escherichia coli β-galactosidase [15,40], GFP [14,18,19] and red fluorescent protein (DsRed) [19], as well as many therapeutic proteins, including coagulation factors VIII [12,16,17] and IX [41][42][43], IL-3 [15,44,45] and IL-7 [46], human growth hormone [41], human erythropoietin (hEPO) [47] and murine erythropoietin (mEPO) [48], arylsulfatase A [49,50], tyrosine hydroxylase GTP cyclohydrolase I [13,51], α-L-iduronidase [52], β-hexosaminidase A [53] and bone morphogenetic protein (BMP) [54]. It remains to be determined how MSCs perform relative to other mammalian expression systems, such as Chinese hamster ovary cells, in terms of transgene expression levels.…”
Section: Mesenchymal Stem Cells As Platforms For Recombinant Protein mentioning
confidence: 99%